Active lifestyle as a reflection of cognitive reserve: The Modified Cognitive Reserve Scale. Issue 3 (3rd July 2021) - Relander, Kristiina; Mäki, Kaisa; Soinne, Lauri; García-García, Juan; Hietanen, Marja
Abstract: Cognitive reserve (CR) refers to individual differences in cognitive processing that can protect from and compensate for functional decline related to ageing or brain pathology. The CR theory postulates that attaining an active and cognitively stimulating lifestyle can accumulate CR. The Cognitive Reserve Scale (CRS) is a questionnaire that measures lifelong attainment in leisure activities. This cross-sectional study aimed to examine the usefulness, validity and reliability of a modified Finnish translation of the CRS, the Modified Cognitive Reserve Scale (mCRS). The mCRS consists of 20 questions concerning studying and information seeking, hobbies and social relationships during three age phases: young adulthood (18–35 years), adulthood (36–64 years) and late adulthood (≥65 years). A group of 69 neurologically healthy adults aged 26–78 filled the mCRS and completed a neuropsychological test battery. We examined the internal consistency of the mCRS and associations between the mCRS, demographical variables and cognitive performance. The mCRS was normally distributed and showed satisfactory internal consistency (Cronbach's alpha 0.81). It was significantly associated with occupation (ԑ 2 = 0.14) and education (rho = 0.51) but not with age or gender. There were significant associations between the mCRS and verbal reasoning (rho = .306), visual reasoning ( r = .319), learning ( r = .293) and inhibition (rho = -.368). Our study suggests that the mCRS is a reliable and valid method to assess lifelong leisure activity. The mCRS is related to other factors that enhance CR, occupation and education, and associated with cognitive performance of healthy adults. It provides an easily administrable means to assess lifelong attainment in stimulating leisure activities.